GREEN HRM AND CSR AS ANTECEDENTS OF ORGANISATION FINANCIAL GROWTH - BECEA, Lavinia-Mihaela; OSOIAN, Codruta (Studia Universitatis Babeș-Bolyai Oeconomica, 2025)
This paper aims to examine the impact of green HRM and corporate social responsibility on financial performance growth, measured by profit, revenue, ROA, and ROE growth. To test the hypotheses, we employed ordinary least squares (OLS) regression analysis. The findings revealed that green HRM is a significant predictor of growth indicators, including profit, ROA, and ROE. Furthermore, contrary to our expectations, the implementation of CSR practices negatively impacts the firm’s potential for economic growth. The empirical evidence shows that CSR is positively associated only with revenue growth. This study contributes to the literature by examining the debated impact of green HRM and CSR on financial performance growth while also offering valuable insights for practitioners and policymakers. JEL classification: M42, O15, J81, Q56